Endothelial dysfunction in patients with different obesity phenotypes - T.V. Sekret; M.V. Vlasenko (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Obesity is a progressive problem in society. The degree of cardiovascular risk in obesity depends on the distribution of adipose tissue, as well as on the endothelial function, since it is endothelial dysfunction that is one of the first links in triggering the development of cardiovascular diseases. The purpose of the study was to determine the functional state of the endothelium in patients with different obesity phenotypes. Materials and methods. During 2019–2021, 88 people were examined: 25 men, 63 women. Their average age was 37.42 ± 11.77 years. A history was collected from all patients in order to determine risk factors for cardiovascular pathology. The blood levels of adipocytokines (leptin and adiponectin) and proinflammatory cytokines (interleukin (ІL) 6, ІL-8, ІL-17) were evaluated using the AU480 biochemical analyzer (Beckman Coulter, Inc., USA). Statistical processing of the results was carried out with the help of the Statistica 7 package (StatSoft, USA). Results. The study had demonstrated that leptin levels in all obesity phenotypes were higher than the reference values of the reagent sets. Consequently, adiponectin level with the progression of visceral obesity was as close as possible to the lower indicators of reference norms. It was found that ІL-17 is an interleukin that triggered an inflammatory reaction in all examined patients. ІL-17 stimulated the activity of pro-inflammatory cytokines ІL-8, ІL-6. The highest cytokine activity was recorded in the presence of visceral obesity without metabolic disorders (phenotype III): ІL-6 was 3.28 ± 1.52 pg/ml, ІL-8 was 96.55 ± 20.30 pg/ml. Due to the activation of the inflammatory reaction, NO synthase is secreted in a state of functional tension, therefore, its level is higher in phenotypes III and IV. Over time, its activity is expected to drop sharply, which will provoke endothelial remodeling. Conclusions. Patients with different phenotypes have a predisposition to endothelial dysfunction. Visceral obesity is the main predictor of the further development of insulin resistance, cardiometabolic disorders, as evidenced by an increase in the level of NO synthase, ІL-17, ІL-8, leptin.